GLUCOSE TRANSPORTER-1 (GLUT-1) IMMUNOREACTIVITY IN BENIGN, BORDERLINE AND MALIGNANT OVARIAN EPITHELIAL TUMORS. - Al-Farah Rehmat Ullah 1, Ayesha Iftikhar 2, Beenish Arif Sultan 3 , Aliya Zaman 4 , Shahida Kashif 5, Zareen Naz 6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT OBJECTIVE: Recent study analyzed GLUT-1 expression in ovarian epithelial tumors by its immunohistochemical implication to distinguish benign, borderline and malignant tumors. STUDY DESIGN: An Analytical Cross-sectional study. PLACE & DURATION: Department of pathology, Basic medical sciences institute (BMSI), JPMC from July 2020 to December 2020. METHODOLOGY: Our study based on the analysis of ovarian tumor samples (irrespective of surgical procedure; except biopsies). Out of 408 cases of histopathologically proven ovarian tumors received in last five years, 72 cases were selected and analyzed further for morphological features, grading and results of immunostaining. Immunohistochemical staining was performed using Rabbit polyclonal antibody. The immunostaining was evaluated and scored by grading the intensity of cell membrane staining and proportion of positive neoplastic cells. Chi-square/fisher exact test (will be applied for values<5) was used to test the association between the intensity and the ovarian epithelial neoplasm, grade and type of lesions. RESULTS: We observed that majority (86.4%) of benign tumors were GLUT-1 negative, while none of GLUT-1 showed GLUT-1 negativity. Consequently, majority (77.8%) of borderline tumors revealed moderate GLUT-1 staining but none of them showed marked staining intensity. In contrast, most of malignant epithelial tumors (56.1%) displayed marked extensive GLUT-1 staining. CONCLUSION: We concluded that GLUT-1 is a useful marker to distinguish benign ovarian tumors from borderline and borderline from their malignant counterparts. Hence, GLUT-1 can be a useful adjunct to the histopathological diagnosis of ovarian epithelial tumors by serving as an objective parameter that can correlate with their biological behavior and possible clinical outcome.